Flipbook-based personal development information service model for enhancing self-awareness in late adolescents - Heriyah, Heriyah; Bundu, Patta; Annas, Suwardi (Goodwood Publishing, 2024)
Purpose: This study aimed to develop a flipbook-based personal development information service model and examine the increase in self-awareness of late adolescents as a measure of its effectiveness Research/methodology: This research used development research methods with an ADDIE design model. The instruments used in this study were validation and practicality sheets, model needs analysis questionnaires, self-awareness questionnaires, interviews, and observations. The data processing used in this research was based on the model's validity and practicality, and N-gain test analysis and Paired Sample t-test using SPSS version 24 were also carried out to evaluate effectiveness. Results: The research results obtained are as follows: 1) assessment of the feasibility of the flipbook-based personal development information service model shows a high validity category with an average value of 91%, and its practicality is considered very practical to use with an average value of 87%; 2) assessment of effectiveness, there is a Sig.2 tailed value of 0.000 < 0.025, so Ho is rejected, and Ha is accepted, as well as an increase in the average (Gain) of pre- and post-test data of 0.60, which is classified as a medium criterion. Based on the research results, the developed product model is effective and contributes to increasing self-awareness among high school students in their late adolescence. Conclusions: The flipbook-based personal development information service model is proven to be valid, practical, and effective in enhancing self-awareness among late adolescents. The product development follows the ADDIE framework and meets the criteria of high validity (91%), high practicality (87%), and effectiveness (N-gain = 0.60; Sig. = 0.000), indicating a statistically significant improvement in students' self-awareness. Limitations: This study is limited to high school students in South Tangerang and does not generalize across broader adolescent populations. The implementation relies on digital literacy and access to stable internet, which may not be consistent across various educational contexts. Contribution: This study introduces a validated flipbook-based model that enhances self-awareness in adolescents through accessible and interactive guidance services.